The Deuteronomic Response to Social Inequality in Ancient Israel and its Relevance to the Urhobo Socio-Cultural Context in Nigeria (2014)
The literary composition of Israel‟s religious history has been attributed to several schools, one of which is the Deuteronomic school with a strong social vision. One of its social visions was the response to social inequality. Existing studies on the Deuteronomic history (Deuteronomy-2Kings) have focused on various levels of redactions and cult centralisation but have not clearly articulated the Deuteronomic response to the phenomenon of social inequality and relevance from the African (Urhobo) socio-cultural perspective. This study, therefore, investigated the Deuteronomic response to social inequality in ancient Israel and its relevance to the Urhobo society. The study was anchored to Gottwald‟s Liberation Hermeneutics which identifies issues of social class, race and gender struggles inherent in biblical text. The Historical-critical method was employed for interpreting the chosen text segments (Deut.1422-29, 169-12,13-15, 2417-18,19-22, 265-15) A purposive sampling method was adopted in administering 400 copies of a questionnaire in three selected local government areas of Urhobo concentrated population in Delta State, namely, Udu, Ughelli South, and Okpe LGAs while three focus group discussion sessions composed of different categories of persons, age and sex were held in three villages: Emadadja, Egbo Uhurie and Orerokpe; chosen to correspond to the LGAs. Data collected were subjected to exegetical analysis using simple percentages. The Deuteronomic response elicited in the text has four main procedures: advocacy for empowerment of the marginalised which transfers the exclusive use of the Tithe from the Priest to caring for the marginal groups (Deut 1422-29) and shift in emphasis of the festivals from solely cultic to sociological purpose (Deut. 1613-15) Others are: emphasis on social justice in Israel‟s judicial system including protection of the marginalised (Deut. 2417-18,19-22) and the tradition-building process which interprets the salvation motif in the exodus tradition as a mandate for a humane society (Deut.265-15) These were proactive and ideological responses against gender bias, class and socio-economic disparity introduced by the monarchical system that put the marginal groups (Levites, orphans, widows and the sojourners) in precarious conditions in the 7th Century. Responses identified in Urhobo setting include Udje dance songs, names and proverbs which advocate equal opportunities, the widow inheritance system, and the culture of extended family support system. Data evidence however suggests changing trends in Urhobo which necessitates a paradigm shift. A total of 171 respondents (56.7%) disagreed that Urhobo inheritance system adequately protects widows, while 263 respondents (87.7%) agreed there are cultural practices that encourage social inequality. The focus group discussion sessions recognised the growing impact of inequality on orphans, widows and increasing poverty. Three aspects of the Deuteronomic Response for the Urhobo society, namely advocacy for protection of the marginal groups, empowerment and social justice are applicable to the religious and cultural situations in Urhobo society. These convergences adequately reflect the social inequalities characterising the Jewish and Urhobo societies